2015
DOI: 10.23953/cloud.ijavst.183
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Structural Characteristics of Selenium Nanoparticles using Lactobacillus Acidophilus Bacteria by Wet Sterilization Process

Abstract: A facile ecofriendly biological approach for the synthesis of selenium nanoparticles using the probiotic Lactobacillus acidophilus bacteria and its characterization is reported in this paper. The synthesized selenium nanoparticles were characterized using UV spectrometer, X-ray diffraction and transmission electron microscopy. The results of X-ray diffraction and transmission electron microscopic studies showed that the nanoparticles were in the uniform size range of 15-50 nm. The present study showed that no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…brevis CRL 2051; 10, Lb. plantarum CRL 2030; while lanes 11 and 17 correspond to F. tropaeoli CRL 2034. has been studied elsewhere (Eszenyi et al, 2011;Sasidharan and Balakrishnaraja, 2014;Visha et al, 2015;Moreno-Martin et al, 2017;Pescuma et al, 2017) showing also NP sizes between 40 and 500 nm depending on the strain used. Contrary to the majority of biosynthetic SeNPs like those reported by Moreno-Martin et al (2017), the nanoparticles produced by our strains were microcrystalline.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…brevis CRL 2051; 10, Lb. plantarum CRL 2030; while lanes 11 and 17 correspond to F. tropaeoli CRL 2034. has been studied elsewhere (Eszenyi et al, 2011;Sasidharan and Balakrishnaraja, 2014;Visha et al, 2015;Moreno-Martin et al, 2017;Pescuma et al, 2017) showing also NP sizes between 40 and 500 nm depending on the strain used. Contrary to the majority of biosynthetic SeNPs like those reported by Moreno-Martin et al (2017), the nanoparticles produced by our strains were microcrystalline.…”
Section: Discussionmentioning
confidence: 96%
“…Contrary to the majority of biosynthetic SeNPs like those reported by Moreno-Martin et al (2017), the nanoparticles produced by our strains were microcrystalline. Also, Visha et al (2015) reported a crystalline structure for the SeNPs produced by a Lb. acidophilus strain; these differences demonstrate the particle diversity produced by LAB.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the concentration of NaHSeO 3 in the medium affected the growth of lactobacilli strains, according to González-Olivares et al (2016) who found that L. rhamnosus GG was more resistant to Na 2 SeO 3 at a concentration of 198 mg/L media; however, L. bulgaricus NCFB2772 showed the lowest assimilation of inorganic selenium (9.14%). Visha et al (2015) also indicated that L.…”
Section: Characterization Of Eco-friendly Senps In Powder Formmentioning
confidence: 97%
“…Several studies have prepared SeNPs using microorganisms (Eszenyi et al, 2011;Kheradmand et al, 2014;Porto et al, 2015Porto et al, , 2019Pusztahelyi et al, 2015;Visha et al, 2015), and the products were evaluated in terms of efficacy. Prokisch and Zommara (2011) produced high-quality SeNPs; Zommara et al (2018) produced biological SeNPs using yoghurt culture, which can be used safely in poultry nutrition and as a biogenic selenium source for humans.…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructures are more active than inorganic forms of selenium, they accumulate better in tissues, easily penetrate the cellular membrane and accumulate in the intracellular space [8,9]. Even at the very low selenium concentrations (0,005-0,1 %), its particles can adsorb antigens and antibodies on the surface.…”
Section: Food Science and Technologymentioning
confidence: 99%